EXTENDED ABSTRACT INTERNATIONAL CONFERENCE SUBMISSION (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
Conceptual representation in the bilingual mind has long been theorized through competing models — yet empirical data from typologically distant, under-resourced language pairs remain sparse. This psycholinguistic study examines how 120 Uzbek-dominant bilinguals residing in the Surkhandarya region organize conceptual knowledge across their two languages, with a specific focus on the directionality and selectivity of conceptual transfer at different L2 English proficiency levels. The study employs a multi-task psycholinguistic battery encompassing semantic priming, translation equivalence judgment, picture-word association, and lexical decision latency measures. Reaction time distributions, error patterns, and cross-linguistic priming asymmetries collectively index the degree to which L1 Uzbek conceptual representations mediate or resist L2 English conceptual access. Guided by the Revised Hierarchical Model and the Distributed Feature Model, the analysis traces how conceptual overlap and divergence between Uzbek and English — particularly across domains where the two languages lexicalize experience differently — shape the mental lexicon's architecture. Preliminary patterns suggest asymmetric conceptual transfer, with L1 Uzbek frames persisting as dominant organizational schemas even at intermediate-to-advanced L2 proficiency, and with specific lexical-semantic domains exhibiting stronger resistance to L2 restructuring than others. These findings carry direct implications for theories of bilingual conceptual representation and for pedagogical models of L2 vocabulary instruction in Central Asian EFL contexts.